Time-Varying Integration Among Asean-5 Economies - Salina H. Kassim; M. Shabri Abd. Majid (Aceh International Journal of Social Science, 2012)
Abstract - This study explores the economic integration among the ASEAN-5 economies over two sample periods; the pre-crisis period (1990 to 1996) and post-crisis period (2000 to 2006). Using the output-price approach, it attempts to determine if the nature of integration among these economies has changed due to the Asian financial crisis in 1997. In methodology, the study adopts the Autoregressive Distributed Lag (ARDL) approach and Vector Error Correction Model (VECM). The results show that the crisis has a deep imprint on the degree of economic integration among these countries. The results provide important inputs for macroeconomic policy formulation at the regional level.